Voluntary postural sway control and mobility in adults with low back pain - Chen, Zhengquan; Tirosh, Oren; Han, Jia; Adams, Roger David; El-Ansary, Doa; Pranata, Adrian (Frontiers in Neuroscience, 2024)
Introduction: Low back pain (LBP) is associated with altered somatosensory perception, which is involved in both involuntary and voluntary control of posture. Currently, there is a lack of methods and tools for assessing somatosensory acuity in patients with LBP. The purpose of this study was (1) to assess the reliability of the sway discrimination apparatus (SwayDA) (2) to evaluate the differences in somatosensory acuity between patients with LBP and pain-free individuals, and (3) to examine relationships between somatosensory acuity, severity of LBP, and mobility in patients with LBP.Methods: Twenty participants (10 patients with LBP and 10 matched asymptomatic controls) were recruited in a test-retest reliability test. Another 56 participants were recruited for this study with 28 individuals presenting with LBP and a further twenty-eight being asymptomatic. The SwayDA was custom-built to measure somatosensory perception during voluntary anterior-posterior (SwayDA-AP), medial-lateral to the dominant side (SwayDA-ML-D), and non-dominant side (SwayDA-ML-ND) postural sway control. Participants also completed mobility tests, including 10 times and 1minute sit-to-stand tests (10-STS, 1m-STS). The area under the receiver operating characteristic curve (AUC) was calculated to quantify somatosensory acuity in discriminating different voluntary postural sway extents.The ICC(2,1) for the SwayDA-AP, SwayDA-ML-D, and SwayDA-ML-ND were 0.741,0.717, and 0.805 with MDC95 0.071, 0.043 and 0.050. Patients with LBP demonstrated significantly lower SwayDA scores (tSwayDA-AP=-2.142, p=0.037; tSwayDA-ML-D=-2.266, p=0.027) than asymptomatic controls. The AUC values of the SwayDA-AP test were significantly correlated with ODI (rSwayDA-AP-ODI= -0.391, p=0.039). Performances on the 1m-STS and the 10-STS were significantly correlated with the AUC scores from all the SwayDA tests (-0.513≤ r ≤0.441, all p<0.05).The SwayDA tests evaluated showed acceptable reliability in assessing somatosensory acuity during voluntary postural sway. Somatosensory acuity was diminished in patients with LBP compared to asymptomatic controls. In patients with LBP, lower somatosensory acuity was associated with increased LBP-related disability. Future research could focus on investigating the factors contributing to the decreased somatosensory perception and mobility in individuals with LBP.